The Influence of School Financial Management on the Effectiveness of Education Programs at MTs Nurul Huda Jakarta - Aslamiyah, Syaibatul (Journal Business Inovation, Accounting and Management, 2025)
This study aims to determine the influence of school financial management on the effectiveness of educational programs at MTs Nurul Huda Jakarta. The method used is a quantitative approach with a correlational research design. The sample in this study consisted of 50 respondents consisting of principals, treasurers, teachers, and administrative staff, who were selected using purposive sampling techniques. The research instrument is in the form of a closed questionnaire that has been tested for validity and reliability. The results of data analysis using simple linear regression showed that school financial management had a positive and significant influence on the effectiveness of the educational program, with a determination coefficient value (R²) of 0,612. This means that 61,2% of the effectiveness of educational programs is influenced by how school finances are managed, while the rest is influenced by other factors. Good financial management, including budget planning, fund allocation, and financial reporting, contributes directly to the implementation of planned, targeted, and sustainable educational programs. This study recommends that schools continue to improve transparency and efficiency in financial management to support the success of education programs in the future.